A Narrative Approach to Both Teaching and Learning About Democracy with Young Children: A Theoretical Exploration - maila dinia husni rahim; Husni Rahim (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
As adults, we often believe that children are only interested with games and children’s ‘stuff’. However research has shown that children do indeed show a greater interest in the world around them, including about politics, elections, and democracy. If we need to teach children about democracy, what are the best methods of teaching democracy to young children? Narrative is considered as an effective medium to convey messages to children and discuss hard subjects. This paper is a theoretical exploration that looks at the narrative approach to teaching and learning about democracy with young children. The researchers has used a literature review to look at why narratives should be used, what narratives should be used and how to use narratives.